Insights into the rotational stability of toric intraocular lens implantation: diagnostic approaches, influencing factors and intervention strategies - Lin, Xuanqiao; Ma, Dongmei; Yang, Jin (Frontiers in Medicine, 2024)
Toric intraocular lenses (IOLs) have been developed to enhance visual acuity impaired by cataracts and correct corneal astigmatism. However, residual astigmatism caused by postoperative rotation of the toric IOL is an important factor affecting visual quality after implantation. To decrease the rotation of the toric IOL, significant advancements have been made in understanding the characteristics of toric IOL rotation, the factors influencing its postoperative rotation, as well as the development of various measurement techniques and interventions to address this issue. It has been established that factors such as the patient’s preoperative refractive status, biological parameters, surgical techniques, postoperative care, and long-term management significantly impact the rotational stability of the toric IOL. Clinicians should adopt a personalized approach that considers these factors to minimize the risk of toric IOL rotation and ensure optimal outcomes for each patient. This article reviews the influence of various factors on toric IOL rotational stability. It discusses new challenges that may be encountered to reduce and intervene with rotation after toric IOL implantation in the foreseeable future.